Music, language and identity in Greece
1 online resource.
Keywords: "The national element in music has been the subject of important studies yet the scholarly framework has remained restricted almost exclusively to the field of music studies. This volume brings together experts from different fields (musicology, literary theory, and modern Greek studies), who investigate the links that connect music, language and national identity, focusing on the Greek paradigm. Through the study of the Greek case, the book paves the way for innovative interdisciplinary approaches to the formation of the 'national' in different cultures, shedding new light on ideologies and mechanisms of cultural policies"--